2017
DOI: 10.1302/2046-3758.68.bjr-2017-0005.r1
|View full text |Cite
|
Sign up to set email alerts
|

Dose optimisation of intravenous tranexamic acid for elective hip and knee arthroplasty

Abstract: ObjectivesWe have increased the dose of tranexamic acid (TXA) in our enhanced total joint recovery protocol at our institution from 15 mg/kg to 30 mg/kg (maximum 2.5 g) as a single, intravenous (IV) dose. We report the clinical effect of this dosage change.MethodsWe retrospectively compared two cohorts of consecutive patients undergoing total hip arthroplasty (THA) or total knee arthroplasty (TKA) surgery in our unit between 2008 and 2013. One group received IV TXA 15 mg/kg, maximum 1.2 g, and the other 30 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 26 publications
(23 reference statements)
1
27
0
Order By: Relevance
“…Sun et al 15 conducted a randomized, controlled trial and reported that a preoperative dose of TXA (15 mg/kg) was as effective as a dose of 10 mg/kg in TBL. In a retrospective study conducted by Morrison et al, 23 a total of 2,537 TKA procedures were included, the patients who received a preoperative dose of TXA (30 mg/kg) led to a significant reduction in transfusion requirement by one-third compared with the group who received the lower dose of 15 mg/kg. It seems a higher dose of TXA would be more effective; however, more prospective studies are in demand for exploring whether continuing to increase the preoperative dose of TXA could further reduce blood loss and transfusion requirement.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al 15 conducted a randomized, controlled trial and reported that a preoperative dose of TXA (15 mg/kg) was as effective as a dose of 10 mg/kg in TBL. In a retrospective study conducted by Morrison et al, 23 a total of 2,537 TKA procedures were included, the patients who received a preoperative dose of TXA (30 mg/kg) led to a significant reduction in transfusion requirement by one-third compared with the group who received the lower dose of 15 mg/kg. It seems a higher dose of TXA would be more effective; however, more prospective studies are in demand for exploring whether continuing to increase the preoperative dose of TXA could further reduce blood loss and transfusion requirement.…”
Section: Discussionmentioning
confidence: 99%
“…Over time the orthopaedic department at Northumbria Healthcare NHS Foundation Trust (NHCT) has introduced a range of interventions aimed at improving post-operative outcomes for patients undergoing elective lower limb arthroplasty. These have been well documented in a series of pre-post cohort studies 13 , 15 , 16 . Details of the interventions and a timeline are given in Table 1 and Figure 1 .…”
Section: Statistical Analysis Planmentioning
confidence: 73%
“…This study is examining short-term outcomes, however, some delays to observed changes in outcomes are expected. The orthopaedic department has previously reported that a 6-month lag period was required to fully adopt the increased TXA dose policy 15 . This same lag will therefore be incorporated into the ITS analysis.…”
Section: Statistical Analysis Planmentioning
confidence: 99%
“…Poeran et al [7] compared four study groups with none, ≤o g, 2 g, and ≥ g of tranexamic acid, and Castro-Menéndeza et al [32] conducted a study with empirical doses of tranexamic acid as high as 2 g and found that 2 g of tranexamic acid iv had the best effectiveness and safety profile. Morrison et al [33] compared 15 mg/kg versus 30 mg/kg intravenous tranexamic acid. While our study did not go higher than 15 mg/kg in terms of dosing, we have found comparable results with the same in terms of rates of transfusion and fall in hemoglobin.…”
Section: Discussionmentioning
confidence: 99%